Perception of Drug Use as a Correlate of Human Immune Deficiency Infection among Students of University of Uyo, Akwa Ibom State - Grace Joe EKA; ONWURAH, Chrysantus Chinyere; Olebuezie Felicia NGOZI; EMEAGUI, Edith Chinedu (Research Parks Publishing LLC, 2020)
The study was carried out to examine the perception of drug use as a correlate of human immune deficiency infection among the students of University of Uyo. Three research questions and three hypotheses were formulated to guide the study. A cross sectional survey design was used. Balloting and simple random sampling technique was used to draw 500 respondents representing the student population of 17,000. A self-developed questionnaire was used for data collection. Mean analysis was used to test the hypotheses. The mean analysis showed increased weight mean scores than the average rating point of 2.50. This indicated that there is actual perception of drug use as a correlate of human immune deficiency infections among the students. The null hypotheses tested showed increased calculated t-value with lesser critical t-value at degree of freedom of 4.98 and .05 alpha level. The null hypotheses were rejected. Based on the findings, it was recommended that seminars, rallies, and workshops be organized to enlighten the students on drug use and HIV/AIDs. School based drug education programmes for the youths in school and appropriate out-of –school based drug education programme should be instituted for the youths. Strengthening and adoption of youth related reproductive health programmes in higher institutions should be established. There should be involvement of governmental and non-governmental organization in fighting against HIV infection. The government should make an unbiased national drug policy for the country against the use and sell of Indian hemp and cigarettes